2011
DOI: 10.1194/jlr.m013789
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative role of LAL, NPC2, and NPC1 in lysosomal cholesterol processing defined by genetic and pharmacological manipulations

Abstract: This article is available online at http://www.jlr.org Nearly all cells in the body, including neurons of the central nervous system (CNS), take up cholesteryl ester (CE) and/or unesterifi ed cholesterol (UC) carried in various lipoproteins from the surrounding pericellular fl uid by receptor-mediated and bulk-phase endocytosis ( 1, 2 ). The sterol in these particles is processed in the late endosomal/lysosomal (E/L) compartment of cells by the sequential action of at least three proteins, lysosomal acid lipas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 44 publications
7
75
0
Order By: Relevance
“…In addition, the similar behaviors of HP-␤ -CD and SBE-␤ -CD to elicit changes in intracellular sterol revealed by altered gene expression suggest that only the "shuttle" capacity of CD is required. This scenario is consistent with proposals that CD is promoting the translocation of unesterfi ed cholesterol from internal membranes of the LE/L across the limiting lysosomal membrane ( 16,17 ) for egress into the cytosolic compartment of Npc1 Ϫ / Ϫ cells.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In addition, the similar behaviors of HP-␤ -CD and SBE-␤ -CD to elicit changes in intracellular sterol revealed by altered gene expression suggest that only the "shuttle" capacity of CD is required. This scenario is consistent with proposals that CD is promoting the translocation of unesterfi ed cholesterol from internal membranes of the LE/L across the limiting lysosomal membrane ( 16,17 ) for egress into the cytosolic compartment of Npc1 Ϫ / Ϫ cells.…”
Section: Discussionsupporting
confidence: 78%
“…Ϫ / Ϫ double-knockout mice ( 17 ). Studies performed within a variety of tissues harvested 24 h after a single HP-␤ -CD injection to 7-or 49-day-old Npc1 Ϫ / Ϫ mice have shown dramatic changes in sterol dynamics, including a decrease in cholesterol synthesis rates, an increase in the ratio of esterifi ed/unesterifi ed cholesterol, downregulation of the sterol regulatory element-binding protein 2 (SREBP2) and its target genes, and increased expression of liver X receptor (LXR) target genes ( 5,18 ).…”
Section: Npc2mentioning
confidence: 99%
“…In vitro studies have shown that CYCLO markedly accelerates cholesterol transfer between membranes via a collisional mechanism involving direct interaction between CYCLO and membranes ( 177 ). The mechanism by which CYCLO releases cholesterol from LEs/Ls was further investigated using two types of ␤ -cyclodextrin ( 167,176 ). Previous studies had shown that CYCLO, at concentrations of >1 mM, removes cholesterol from membranes into the aqueous medium by formation of a 2:1 CYCLO-cholesterol molar complex.…”
Section: Discussionmentioning
confidence: 99%
“…At lower concentrations (<1 mM), however, both CYCLO and sulfobutylether-␤ -cyclodextrin can shuttle cholesterol between membranes ( 171 ). To determine whether CYCLO removed cholesterol from LEs/Ls of NPC-defi cient cells by solubilization or by a shuttle mechanism, Npc1 Ϫ / Ϫ mice were injected with CYCLO or sulfobutylether-␤ -cyclodextrin ( 167,176 ). With both types of cyclodextrin, the mobilized cholesterol did not rapidly and prolongs life are very encouraging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation